Potential of Endophytic Bacteria as Biocontrol of Colletotrichum coffeanum F.Noack Fungus Causing Anthracnose in Arabica Coffee (Coffea arabica L.) in Vitro - Setiawan, Bagus; Warsito, Kabul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Indonesia is the fourth largest coffee producing country in the world. However, Indonesian coffee production has decreased due to disease caused by Colletotrichum coffeanum F.Noack. This research aimed to utilize endophytic bacteria as biocontrol to inhibit growth and development of Colletotrichum coffeanum F.Noack.. The endophytic bacteria used came from the isolation of Arabica coffee plant stems. The isolation results obtained were 5 isolates with different characteristics. Based on the results of the antagonist test, there are 2 out of 5 endophytic isolates that have the potential to inhibit pathogen growth. The results of the largest inhibition zone were 17,18mm in Sp.BS2 and the results of the smallest inhibition zone were 14,98 mm in Sp.BS5. In the growth rate of endophytic bacteria, the largest value is 351 x 1015 in isolate Sp.BS5 in 48 hours and the smallest value is 8 x 105 in isolate Sp.BS5 in 6 hours. In the IAA (Indole Acetic Acid) test results, the largest value is 66.36 ppm in treatment P1J3 (pH 6.5; 72 hours) and the smallest value is 26.89 ppm in treatment P3J3 (pH 7.5; 72 hours). The results of these values indicate that endophytic bacterial isolates from Arabica coffee plant stems have the potential to inhibit the growth of Colletotrichum coffeanum F.Noack.